Double-Track Entrepreneurial Education Model to Improve Independence Among Students of Islamic Boarding School in Malang - Agung Winarno; Desy Nadia (Universitas Negeri Malang, 2021)
This research aims to describe an entrepreneurship education model carried out in the boarding school which includes the process of instilling independent values, the management, and the obstacles during the implementation of education model. This research employed qualitative descriptive method with a case study approach. The participants of this research were the entire stakeholders in Bahrul Maghfiroh Islamic Boarding School Malang. The key informants of this research were the leader of the boarding school, teachers, and the students. The data analysis employed 6P simultaneous stages which include approach, discovery, comprehending, conforming, interpreting, and presenting. The research results show that the implementation of entrepreneurship education which applies double-track education model enables students to prepare them entrepreneurship theory in classroom and allows them to acquire actual practices in carrying out business activities in the real-life context. This model, furthermore, allows students to improve their independent thinking and creativity in carrying out business. However, this program has several obstacles to overcome such as a limited movement of students in accessing technology during the study in the boarding school.